2012
DOI: 10.1002/cae.20396
|View full text |Cite
|
Sign up to set email alerts
|

Matlab based simulation toolbox for the study and design of induction motor FOC speed drives

Abstract: A new Matlab/Simulink based simulation toolbox for studying and designing induction motor field oriented control schemes is proposed in this article. It has advantages over other previous works published since it is modular, flexible, interactive, easy to use, and the results are closer to the experimental ones because it takes into account real complex effects, such as: motor core saturation, parameter variations with the speed and temperature, sensor signal digital processing, and inverter real voltage wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Several simulation software packages exist for running CBS in engineering education. We selected MATLAB/SIMULINK and FER software [9,26]. The first one represents a complete simulation environment for studying the EHS‐s, and, due to its popularity and prevalence, is becoming a necessity in engineering practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several simulation software packages exist for running CBS in engineering education. We selected MATLAB/SIMULINK and FER software [9,26]. The first one represents a complete simulation environment for studying the EHS‐s, and, due to its popularity and prevalence, is becoming a necessity in engineering practice.…”
Section: Methodsmentioning
confidence: 99%
“…CBS promotes active learning and motivates learners to perform better because of their involvement in practical experiences related to concrete engineering problems. Additionally, CBS promotes reflective observation of transition processes and phenomena not directly observable by human senses, virtual experiential testing, schema construction, development of models of engineering systems, etc… CBS can also provide the learner with quick feedback throughout the learning process, which can guide them in the achievement of specific goals . However, some research studies reported in academic literature have found that CBS does not always enhance learning.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is the state-of-the-art simulation technology today as used in many simulation environments like MATLAB/Simscape and Modelica. Paper [4] describes an induction motor simulation model, including control algorithms and their implementations in MATLAB/Simulink. Studies [5][6][7] focus on the application of MBD methods with emphasis on motor control software development.…”
Section: Introductionmentioning
confidence: 99%
“…EES is used to solve several practical examples in thermal engineering . Other studies propose the use of Matlab or Simulink due to their widespread capabilities .…”
Section: Introductionmentioning
confidence: 99%